Prevalence of chronic respiratory disease using case-finding tools in adults living with noncommunicable disease in low- and middle-income countries: a systematic review - Adriano Petrolini-Mateus; Gustavo Henrique Guimarães Araujo; Nathany Souza Schafauser-Segundo; Naiara Tais Leonardi; Viviane Castello-Simões; John R. Hurst; Renata Gonçalves Mendes (BMC Pulmonary Medicine)
Abstract Background Chronic respiratory diseases (CRD) often coexist with other non-communicable diseases (NCD) and are responsible for nearly three-quarters of all deaths in low- and middle-income countries (LMIC). People living with NCD are considered at higher risk of having CRD, but the prevalence of CRD in those with other NCD in LMIC is not well described. This study aimed to identify the prevalence of CRD and/or abnormal spirometry identified through case-finding tools in adults living with NCD in LMIC. Methods This systematic review followed the PRISMA guidelines and included Lilacs, PubMed, Scielo, Embase and Web of Science databases. Two reviewers independently examined the titles and abstracts of studies identified from the search to determine eligibility for inclusion. Searching was carried out until May 16, 2024, and was updated in February 2025. Cross-sectional studies that used case finding tools to identify CRD in adults living with other NCD in LMIC were eligible. The studies were exported to Rayyan software, and duplicates were manually removed. Data were extracted including study characteristics, and quality was assessed using the modified Newcastle-Ottawa Scale risk of bias tool. A descriptive analysis of the prevalence of respiratory diseases and spirometric abnormalities was reported considering 95% confidence intervals. Results A total of 8,939 citations were screened based on titles and abstracts. Thirteen full-text articles were assessed for eligibility. Five studies were excluded for not providing sufficient data, two for inadequate outcome ascertainment, two for being conducted in developed countries, and one for only including patients with a previous COPD diagnosis. Three cross-sectional studies met the inclusion criteria, one conducted in India, and two in Brazil. Considering studies with a low risk of bias, the prevalence of CRD was between 1% and 5.2% in patients with hypertension. The prevalence of abnormal spirometry was between 11% and 17% in patients with coronary artery disease. Conclusion The prevalence of CRD identified through case-finding tools in adults with NCD in LMIC varies according to the NCD in which it was investigated. These findings highlight the opportunity to case-find CRD by assessing people accessing care for other NCD. Registration PROSPERO 2024 CRD42024534734.